Efektivitas Penyuluhan Kesehatan Reproduksi, HIV dan AIDS, Dan Pencegahan Bullying Terhadap Pengetahuan Dan Sikap Remaja Di SMAN 1 Kendari - Yusran, Sartiah; Milida, Rizkia; Karimuna, Siti Aisyah; Siradjudin, Sarah Soraya; Rahmatiah MZ, Siti Syaqinah; Zul, Wa; Saleh, Akhmad (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2026)
Background: Lack of knowledge about health, the influence of family and peer environments, and lack of access to comprehensive education about sexual and reproductive health make adolescents highly vulnerable to reproductive health problems. Risky sexual behavior, teenage pregnancy, sexually transmitted infections, HIV/AIDS, and psychosocial problems such as abuse are driven by these conditions. Given the large number of adolescents in Indonesia and their role in determining the quality of the future demographic bonus, organized school-based reproductive health education interventions are necessary. As a result, the reproductive health education program at SMAN 1 Kendari is very important to prevent, instill positive beliefs, and encourage adolescents to become healthy and responsible individuals. Objective: To assess the increase in knowledge and attitudes of ninth-grade students at SMAN 1 Kendari toward reproductive health, HIV and AIDS, and the prevention of bullying and human trafficking. Methods: This study was a community service activity with a one-group pretest–posttest design. The research subjects were 34 students in class XI A at SMAN 1 Kendari. The intervention was carried out through interactive lectures, discussions, and audiovisual media. Data analysis was performed using the Wilcoxon test for attitude data and the Sign Test for knowledge data. Results: There was a significant increase in students' attitudes towards reproductive health and the prevention of risky behavior (p < 0.001). Knowledge about types of bullying increased significantly (p = 0.016). Knowledge about HIV and AIDS was generally good since the pretest, with an increase in certain misconceptions.